Can discreet performance banding, as compared to bio-banding, discriminate technical skills in male adolescent soccer players? A preliminary investigation. Issue 2 (April 2022) - Moran, Jason; Cervera, Victor; Jones, Benjamin; Hope, Edward; Drury, Ben; Sandercock, Gavin
Maturation-related changes in body dimensions and performance can lead to physical mismatches and drop out from youth sport. Here, we propose a new method termed 'discreet performance banding' (DPB). We aimed to determine if dividing youths by actual physical performance of a discreet skill or ability ('change or direction' [COD] ability) could discriminate between the most and least skilled players better than a marker of implied performance, such as an assessment of biological maturation. 182 male academy Spanish soccer players (age: 13-18 years height: 143 to 188 cm; mass: 32.3 to 81.4 kg) were divided into maturation groups (Tanner stages 2 through 5) and COD groups ('fast', 'intermediate' and 'slow'). Players' skills (passing, shooting, ball control) were evaluated on a six-point scale with a value of '1' considered 'very bad' and a value of '6' as 'very good'. When divided by maturity status, analyses revealed no significant differences between groups in soccer skill. However, when divided into COD groups, the analyses revealed significant differences between the fast and intermediate players ([p < 0.001] favouring the fast group) and between the intermediate and slow players ([p < 0.026] favouring the slow group). There was no significant difference in skill between the fast and slow groups, though the fast group demonstrated a higher skill level as indicated by a small effect size. Fast players were more skilful than both the intermediate and slower players, indicating that COD status can be a differentiating factor between players of different skill levels. DPB could be used to equalise competition in youth sport and to enhance the overall level of enjoyment that youths derive from engagement in sport.